The Liability of Notaries in the Execution of Hybrid Deeds: A Review of Compliance with the Notary Law and Notarial Code of Ethics - Al-Fath, Tahega Primananda; Genial, Reynaldi Putra (Journal of Law, Politic and Humanities, 2025)
The execution of authentic deeds by notaries is a legal function endowed with the highest evidentiary value. However, technological advancements and the demand for efficient legal services have prompted the emergence of hybrid deed practices, which combine online and offline processes. Although innovative, this practice raises legal concerns due to its inconsistency with the principle of physical appearance as mandated in Article 16 paragraph (1) letter m and Article 38 of the Notary Position Act (UUJN). This article examines the scope of notarial liability in the drafting of hybrid deeds that fail to comply with the formal requirements set out in the UUJN. Based on a normative juridical approach, it is found that the substitution of physical appearance and signature before a notary with hybrid procedures constitutes a legal violation, triggering three forms of liability: civil, criminal, and administrative. Notaries may face civil lawsuits for breach of contract or unlawful acts, criminal prosecution for forgery, and ethical sanctions by the Notary Supervisory Council.